Low field domain wall dynamics in artificial spin-ice basis structure - Lim, Gerard Joseph (2015)
Artificial magnetic spin-ice nanostructures provide an ideal platform for the observation of magnetic monopoles. The formation of a magnetic monopole is governed by the motion of a magnetic charge carrier via the propagation of domain walls (DWs) in a lattice. To date, most experiments have been on the static visualization of DW propagation in the lattice. In this paper, we report on the low field dynamics of DW in a unit spin-ice structure measured by magnetoresistance changes. Our results show that reversible DW propagation can be initiated within the spin-ice basis. The initial magnetization configuration of the unit structure strongly influences the direction of DW motion in the branches. Single or multiple domain wall nucleation can be induced in the respective branches of the unit spin ice by the direction of the applied field.